ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN PJOK PADA MASA PANDEMI COVID-19 DI SMPN 64 BANDUNG - Putri Ganesha, - (2022)
The covid-19 pandemic is a tragedy that has grieved the entire population of the earth. Many countries have decided to close schools, colleges and universities, including Indonesia. All learning is done at home online. Learning activities are still carried out in order to know the learning of students. The purpose is study was to analyze what students' learning difficulties were in learning Physical Education during the Covid-19 pandemic. This research method uses descriptive quantitative method and uses probability sampling technique (simple random sampling). With a sample of 71 students of class IX SMPN 64 Bandung and data collection tools used in the form of a questionnaire using google form. Students' learning difficulties in learning Physical Education online, which are most often experienced by students are technical difficulties, learning implementation, students' external and internal difficulties.